2010
DOI: 10.1182/blood-2010-03-276261
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-7 treatment counteracts IFN-α therapy-induced lymphopenia and stimulates SIV-specific cytotoxic T lymphocyte responses in SIV-infected rhesus macaques

Abstract: Interferon-␣ (IFN-␣)-based therapy ispresently the standard treatment for hepatitis C virus (HCV)-infected patients. Despite good effectiveness, this cytokine is associated with major side effects, including significant lymphopenia, that limits its use for HIV/HCV-coinfected patients. Interleukin-7 (IL-7) has recently shown therapeutic potential and safety in several clinical trials designed to demonstrate T-cell restoration in immunodeficient patients. The purpose of this study was to evaluate, in simian immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 48 publications
0
22
1
Order By: Relevance
“…The use of adjuvants such as IL-7 [69] that may counteract some of the lymphopenic effects of IFN-α may sustain functionality of CD4 and CD8 T cells and improve treatment efficacy. We have shown in this study that baseline levels of CD127 expression and antigen specific proliferation may together provide good predictors of the response to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The use of adjuvants such as IL-7 [69] that may counteract some of the lymphopenic effects of IFN-α may sustain functionality of CD4 and CD8 T cells and improve treatment efficacy. We have shown in this study that baseline levels of CD127 expression and antigen specific proliferation may together provide good predictors of the response to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral blood cell phenotype was analyzed from frozen whole blood by flow cytometry using a BD FACS CANTO II (BD Biosciences, Le Pont de Claix, France) as described (41). The fluorochrome-conjugated antibodies used for polycromatic flow cytometric analysis are listed in Table S3 in Supplementary Material.…”
Section: Methodsmentioning
confidence: 99%
“…Alpdogan et al [56] demonstrated the immune reconstitution effects of IL-7 administration in a mouse model of allogeneic HSCT and Storek et al did the same in a baboon model of autologous transplant [57]. This impressive immune reconstitution potential is also well documented in three reports on SIV-infected monkeys [5860] and has more recently been shown to counteract interferon-induced lymphopenia [61]. In all these models, reconstitution involves both CD4 and CD8 lymphocytes as well as naïve and memory T cells.…”
Section: Il-7 Key Preclinical Results Support Its Therapeutic Usementioning
confidence: 97%
“…The cytokine lead to an upregulation of homing chemokine receptors on T cells including CXCR4, CCR6, and CCR9 coupled with increased chemokine levels in tissues (CCL19, CCL20, CCL21, and CCL25) and plasma (CCL3, CCL4, and CXCL12). The teams of Li et al and Pellegrini et al, elegantly demonstrated that IL-7 treatment of mice induces a massive T cell infiltration in murine tumor leading to an enhanced anti-tumor protection correlated with an increased number of activated dendritic cells [61, 62]. Moreover, IL-7 will decrease the immunosuppressive environment in the tumor by decreasing TGFbeta secretion a key cytokine for immunosuppressive Treg.…”
Section: Il-7 Key Preclinical Results Support Its Therapeutic Usementioning
confidence: 99%